1994
DOI: 10.1113/jphysiol.1994.sp020418
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of chloride conductance increase to slow EPSC and tachykinin current in guinea‐pig myenteric neurones.

Abstract: 1. Single electrode voltage clamp recordings were obtained from myenteric neurones of guinea-pig ileum in vitro. Slow excitatory postsynaptic currents (sEPSCs) were elicited by focal stimulation of interganglionic nerve strands in twenty-four of thirty neurones more than 30 min after impalement. In seventeen of twenty-four neurones, sEPSCs were associated with a conductance decrease and reversed polarity at -96 + 3 mV (near the reversal potential for potassium, EK); this response was due to inhibition of resti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 32 publications
(59 reference statements)
2
39
0
Order By: Relevance
“…SP activates voltage-dependent Ca 2ϩ channels, voltage-dependent K ϩ conductances, Cl Ϫ currents, Ih currents, voltage-dependent Na ϩ channels, and nonselective cationic channels (Adams et al, 1983;Stanfield et al, 1985;Bley and Tsien, 1990;Shen and North, 1992;Bertrand and Galligan, 1994;Aosaki and Kawaguchi, 1996). In most neurons, SP depolarizes membrane potential by decreasing resting K ϩ conductances (Akasu et al, 1996;Lepre et al, 1996;Ptak et al, 2000;Yasuda et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…SP activates voltage-dependent Ca 2ϩ channels, voltage-dependent K ϩ conductances, Cl Ϫ currents, Ih currents, voltage-dependent Na ϩ channels, and nonselective cationic channels (Adams et al, 1983;Stanfield et al, 1985;Bley and Tsien, 1990;Shen and North, 1992;Bertrand and Galligan, 1994;Aosaki and Kawaguchi, 1996). In most neurons, SP depolarizes membrane potential by decreasing resting K ϩ conductances (Akasu et al, 1996;Lepre et al, 1996;Ptak et al, 2000;Yasuda et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…An involvement of Cl Ϫ conductance is also unlikely (Bertrand and Galligan, 1994), because the equilibrium potential for the Cl Ϫ ions would be less than Ϫ52 mV, which is close to the resting membrane potential of the neurons, assuming that the ion concentrations of the cells become almost equal to that of the patch-pipette solution. Although our experiments by no means excluded the possible blocking actions of SP on channels such as K ϩ and Ca 2ϩ at the suprathreshold levels, our findings strongly imply that the SP-induced TTXinsensitive cation current accounts for virtually all of the inward current at rest in the large aspiny interneurons.…”
Section: Discussionmentioning
confidence: 99%
“…Electrophysiological studies on neurons in the other brain areas have shown that SP modulates several ionic conductances, and that the ionic mechanisms of SP actions differ considerably among neuronal types (Adams et al, 1983;Stanfield et al, 1985;Bley and Tsien, 1990;Shen and North, 1992;Bertrand and Galligan, 1994).…”
mentioning
confidence: 99%
“…Previous investigations have determined that NK 1 and NK 3 receptors mediate prolonged depolarizations in the myenteric plexus of the intestine and that tachykinins likely contribute to slow EPSPs in myenteric neurons (1,25,26). Because the result of the experiments in the presence of TTX indicated that a component of the PGE 2 -mediated depolarization may be indirect and due to release of neuroactive compounds from nearby nerve terminals, additional experiments were conducted to investigate a possible role of tachykinins in the generation of the indirect or presynaptic effects of PGE 2 observed in myenteric AH cells.…”
Section: Nk Receptor Antagonists Significantly Inhibit Pge 2 -Mediatementioning
confidence: 99%